#Grateful: Longitudinal Associations Between Adolescents' Social Media Use and Gratitude During the COVID‐19 Pandemic. (26th August 2021) - Maheux, Anne J.; Nesi, Jacqueline; Galla, Brian M.; Roberts, Savannah R.; Choukas‐Bradley, Sophia
Abstract : During the COVID‐19 pandemic, some ways of using social media—such as directly communicating with friends—may have helped adolescents thrive. We examined longitudinal associations between high school adolescents' social media use and gratitude across a 15‐month period before and during the pandemic ( n  = 704, M age  = 15.10; 52% girls). The trajectories of gratitude and the importance of social media for meaningful conversations with friends—but not frequency of social media use—were positively associated over time. At the within‐person level, gratitude predicted increased importance of social media for meaningful conversations, but not vice‐versa. Findings suggest that gratitude may be associated with and may motivate using social media to foster social connection, but may not increase overall social media use.